The Johnson Collection of Arab-Sasanian Coins. - Malek, Hodge Mehdi. (London)
2 cilt (1. c. li, 422 sayfa ; 2. c. x, sayfa 423-759)
Keywords: “This is the first major work to attempt a comprehensive study of the Arab-Sasanian silver coinage since Walker's 1941 Catalogue of the British Museum collection. It includes the latest research on the subject, both historical (chapters 1-4) and numismatic (chapters 5-15). All the coins (over 1,600), both silver drachms and copper fulus, in the Johnson collection are illustrated on the excellent plates. Where the Johnson collection does not have a specimen of an important coin an example is illustrated from another source, making this a truly important work“ -- Yayıncı.